Childhood emotional neglect predicts empathic accuracy in social inclusion and exclusion contexts. Issue 4 (24th April 2022) - Zhang, Xuehan; Zhang, Mengning; Zeng, Mei; Lan, Mengxue; Liu, Yadong; Li, Jiwen; Chen, Haopeng; Yang, Juan
Abstract: Previous studies have shown that individuals with a history of childhood emotional neglect show impaired empathy. However, accurately identifying emotions in others is an essential aspect of empathic functioning. The current study aimed to investigate the influence of childhood emotional neglect on empathic accuracy. A total of 92 participants were recruited from a local university. Forty‐six participants were randomly assigned to the social exclusion context (SE), and the other 46 were assigned to the social inclusion context (SI). The Childhood Trauma Questionnaire was used to measure childhood emotional neglect. Participants observed real interpersonal communications in which their in‐group members were either socially included or excluded and evaluated the extent of the emotion they felt for their in‐group members. Results found participants empathized with a high level of positive emotion in the SI context ( t = 8.13, p < .001) and negative emotion in the SE context ( t = 10.76, p < .001) in general. Moreover, childhood emotional neglect decreased the empathic accuracy in both contexts (SI context: β = −0.42, SE = 0.04, p = .004; SE context: β = −0.38, SE = 0.04, p = .009). These results contribute to the current understanding of social functioning of childhood emotional neglect in specific contexts.